Analysis of Threats and Implications of Climate Change on Sharks - Rojas, José Rodrigo (2012)
The vulnerability is a function depending on exposure, sensibility and adaptative capacity. This concept is applied to the study of the threats facing sharks for eco-trophics changes caused by climate change. The approach of this research discusses the dichotomy between the evolutionary characteristics, life strategies and domain of these chondrichthyan versus systemic and irreversible transformations imposed by this megaescala phenomenon. Worldwide evidence shows that climate change is an intense and constant vector of eco-systemic modifications even beyond of shark’s life strategies, pushing them to resilience limits over reproductive cycles, food supply, refugia, growth rates and patterns of dispersion. The evolutionary roadmap that led the sharks to dominate aquatic environments confronts them with threats exceed the capacity to effective answer.